Effect of tunneling defects on the joint strength efficiency obtained with FSW - Baloš, Sebastian (Materiali in tehnologije, 2014)
In this paper, an attempt was made to study the effects of various types of tunneling defects in friction stir welding (FSW). Two types of welding tool were used, one with a threaded and the other with a polygonal pin. To enable the formation of tunneling defects, the shoulder-to-pin-volume ratio was larger than 1 for both tools, while the ratio of rotation speed to welding speed was optimized as well. Tunneling defects were tested on EN-AW 5052 H32 and H38 alloys, having the thicknesses of 3 mm and 8 mm. It was found that the threaded tool produced a single or double triangular, as well as crack-shaped tunnel. The polygonal tool produced a multiple triangular tunnel (the material flows toward the weld face) with a complex shape or a crack-type tunnel with a complex shape. The most unfavorable tunnel obtained with the polygonal tool was the crack-shaped one, resulting in the 62 % and 46 % joint yield and ultimate tensile-strength efficiency. The corresponding values for the threaded tool were 40 % and 36 %. The hardness efficiencies did not follow the trends of the proof and ultimate tensile strengths due to the prevention of the tunneling during indentation. Another effect on the hardness is the presence of microcracks that may influence the apparent decrease in the hardness in spite of the detected grain-refinement effect in the nugget. These effects influence the hardness distribution in the weld, shifting the maximum hardness value into the thermo-mechanical zone.
Keywords: drsno mešalno varjenje; friction stir welding; aluminijeve zlitine; aluminium alloy; aluminium alloys; tunelska napaka; tunneling defect; joint strength; trdnost spoja